Mengarungi Gelombang Digital: Peran Self-compassion dan Gratitude Terhadap Online FoMO Pada Mahasiswa - Raidah Hanifah; Saikhoni Saikhoni; Meilia Wigati; Rima Wilantika; Muhammad Lathief Syaifussalam (Jurnal Psikologi Perseptual)
This research aims to determine the role of self-compassion and gratitude on online FoMO in students. Testing the hypothesis in this research uses multiple linear regression analysis. The subjects in this research were 257 students in Lampung, Indonesia. Partially, in this research, the results showed that there was a very significant role between self-compassion and online FoMO, p = 0.007 and t value of -2.272. The partial test of the second hypothesis resulted in a very significant role between gratitude towards online FoMO p = 0.004 with a t value of -2.931. Based on the multiple linear regression test, the results showed that there was a very significant role between self-compassion and gratitude on online FoMO in students (F = 10.916, significance 0.000 p0.001). This means that the higher the compassion and gratitude, the lower the online FoMO and vice versa. The contribution of the effective variable self-compassion to online FoMO was 7.6% and the effective contribution of gratitude to online FoMO was 10.1%.